Sporadic clone Escherichia coli ST615 as a vector and reservoir for dissemination of crucial antimicrobial resistance genes - Carrera Páez, Laura Camila; Olivier, Martin; Gambino, Anahí Samanta; Poklepovich, Tomás; Aguilar, Andrea Pamela; Quiroga, María Paula; Centrón, Daniela (Frontiers in Cellular and Infection Microbiology, 2024)
There is scarce information concerning the role of sporadic clones in the dissemination of antimicrobial resistance genes (ARGs) within the nosocomial niche. We confirmed that the clinical Escherichia coli M19736 ST615 strain, one of the first isolates of Latin America that harbors a plasmid with an mcr-1 gene, could receive crucial ARG by transformation and conjugation using as donors critical plasmids that harbor blaCTX-M-15, blaKPC-2, blaNDM-5, blaNDM-1, or aadB genes. Escherichia coli M19736 acquired blaCTX-M-15, blaKPC-2, blaNDM-5, blaNDM-1, and aadB genes, being only blaNDM-1 maintained at 100% on the 10th day of subculture. In addition, when the evolved MDR-E. coli M19736 acquired sequentially blaCTX-M-15 and blaNDM-1 genes, the maintenance pattern of the plasmids changed. In addition, when the evolved XDR-E. coli M19736 acquired in an ulterior step the paadB plasmid, a different pattern of the plasmid’s maintenance was found. Interestingly, the evolved E. coli M19736 strains disseminated simultaneously the acquired conjugative plasmids in different combinations though selection was ceftazidime in all cases. Finally, we isolated and characterized the extracellular vesicles (EVs) from the native and evolved XDR-E. coli M19736 strains. Interestingly, EVs from the evolved XDR-E. coli M19736 harbored blaCTX-M-15 though the pDCAG1-CTX-M-15 was previously lost as shown by WGS and experiments, suggesting that EV could be a relevant reservoir of ARG for susceptible bacteria. These results evidenced the genetic plasticity of a sporadic clone of E. coli such as ST615 that could play a relevant transitional link in the clinical dynamics and evolution to multidrug/extensively/pandrug-resistant phenotypes of superbugs within the nosocomial niche by acting simultaneously as a vector and reservoir of multiple ARGs which later could be disseminated.